London falling [large type] - Cleeton, Chanel (Cleeton, Chanel. International school series, 2024)
"The smoldering connection between Maggie and Samir sparks into flame at London's International School in London Falling, now available for the first time in print! When Maggie Carpenter left the seductive glitz of London for summer break in her small South Carolina hometown, she walked away from the most intense encounter of her life. But now that she's returned to the International School--and sexy, privileged Samir Khouri is once again close enough to touch--she can't help but remember the attraction, the drama...the heartbreak. Samir can't afford to fall for someone so far removed from his world, not when his time in London is running out. It's his last chance at freedom before he returns home to Lebanon, where he'll be expected to follow in his father's footsteps. But when a scorching secret hookup with Maggie becomes a temptation neither one can resist, they'll both have to fight to survive the consequences...if they want a future together"--